2023
DOI: 10.1186/s12978-023-01635-7
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of the Safe Delivery Application on knowledge and skills managing postpartum haemorrhage in a low resource setting: a cluster randomized controlled trial in West Wollega region, Ethiopia

Abstract: Background Postpartum haemorrhage is one of the leading causes of maternal mortality in low-income countries. Improving health workers' competencies in obstetric emergencies in low-income settings, has been recognized as an important factor in preventing maternal mortality and morbidity. mHealth interventions in maternal and newborn health care has shown the potential to improve health service delivery. Strong study designs such as randomized controlled trials are missing to estimate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…After publication of this article [ 1 ], the authors reported that in the ‘Methods’-section, subsection ‘Intervention’, first sentence, it should say ‘second and last author’ instead of ‘first and last author’.…”
mentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that in the ‘Methods’-section, subsection ‘Intervention’, first sentence, it should say ‘second and last author’ instead of ‘first and last author’.…”
mentioning
confidence: 99%